TA'AWUN EDUCATION AND COLLECTIVE WELL-BEING AMONG YOUNG WOMEN CADRES OF NASYIATUL AISYIYAH - Uswatun Hasanah; Itsna Nurrahma Mildaeni; Retno Dwiyanti; Tri Naimah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Young women cadres in faith-based community organizations often navigate multiple roles as students, workers, wives, mothers, and organizational activists. This study examines role conflict among young cadres of Nasyiatul ‘Aisyiyah (NA), a young women’s autonomous organization within Muhammadiyah, and explores how the Islamic relational value of ta’awun, or mutual assistance in doing good, contributes to their collective well-being. A descriptive qualitative design was employed using data from 125 cadres across Indonesia through an online questionnaire, in-depth interviews, and ongoing focus group discussions. Closed-ended responses were summarized descriptively, while open-ended responses and interview data were inductively coded to remain grounded in participants’ own accounts. The findings indicate that role conflict is particularly pronounced between organizational responsibilities and employment, generating time pressure, guilt, and emotional exhaustion. Ta’awun is practiced through task redistribution, emotional support, and flexible participation, strengthening belonging, solidarity, and organizational commitment, although its implementation varies across regions and leadership levels. A tentative model linking role conflict, ta’awun-based coping, collective well-being, and organizational commitment is proposed